Teoria da coerência central: atribuição de estado mental e rastreamento visual - Tassini, Susanny Cristini Vercellino [UNIFESP] (2021)
Introduction: Central Coherence Theory (CCT) is a cognitive process associated with an individual's ability to identify a whole from its parts. In social context, it would be involved in the interpretation of emotional clues and attribution of mental state. A weak CCT has been considered part of the neurocognitive phenotype in Autism Spectrum Disorder (ASD), but it has been less investigated in comparison to other processes such as Theory of Mind. Objective: of this study was to investigate CCT processes in the ASD from the recognition of visual stimuli with greater or lesser demand for social processing. Method: Fifty-three male subjects participated in the study, 28 (25.53 ± 4.98 years old) with diagnosis of ASD and 25 (26.60 ± 3.87 years old) controls. All were submitted to a task of recognition of visual stimuli associated with the analysis of visual tracking patterns using Eye-tracker technique. The stimuli with lower social processing demands included Navon-type letter figures, as well as superimposed or fragmented figures from standardized tests. The stimuli with the highest social demand were drawings of scenes of social interaction situations. Quantitative analyses (GLzM) were used for measures such as number of hits, reaction time and duration of responses.The pattern of eye tracking was analyzed using a heat map (route of the gaze to recognize the image), fixation of the gaze by quadrants. Qualitative analyzes (of thematic and semiotic content) were used to categorize verbal reports in the description of scenes of interaction. Results: they revealed a pattern of fixation of the quadrants in the participants with ASD different from that of the controls, had a longer reaction time and spent more time in the report. The qualitative analysis revealed a clear tendency to focus on details both of scenes with social content and of stimuli with less social content, impairing the interpretation of the context. Therefore, the findings seem to corroborate evidence of a weak CBT in high functioning autism, which may contribute to the weaknesses in the interpretation of social contexts in this clinical condition. Conclusion: The results are within the scope of the hypothesis that individuals in the clinical group would have greater difficulty in recognizing and interpreting social content.